Performance Evaluation of Adaptive Continuous Wavelet Transform based Rake Receiver for UWB Systems - Ch. Navitha; K. Sivani; K. Ashoka Reddy (Institute of Advanced Engineering and Science, 2018)
This paper proposes an adaptive continuous wavelet transform (ACWT) based Rake receiver to mitigate interference for high speed ultra wideband (UWB) transmission. The major parts of the receiver are least mean square (LMS) adaptive equalizer and N-selective maximum ratio combiner (MRC). The main advantage of using continuous wavelet rake receiver is that it utilizes the maximum bandwidth (7.5GHz) of the UWB transmitted signal, as announced by the Federal Communication Commission (FCC). In the proposed ACWT Rake receiver, the weights and the finger positions are updated depending upon the convergence error over a period in which training data is transmitted. Line of sight (LOS) channel model (CM1 from 0 to 4 meters) and the Non line of sight (NLOS) channel models (CM, CM3 and CM4) are the indoor channel models selected for investigating in this research . The performance of the proposed adaptive system is evaluated by comparing with conventional rake and continuous wavelet transform (CWT) based rake. It showed an improved performance in all the different UWB channels (CM1 to CM4) for rake fingers of 2, 4 and 8. Simulations showed that for 8 rake fingers, the proposed adaptive CWT rake receiver has shown an SNR improvement of 2dB, 3dB, 10dB and 2dB respectively over CWT rake receiver in different UWB channels CM1, CM2, CM3 and CM4.